THE ROLE OF ULTRASOUND AND MRI IN DIAGNOSING FETAL ANOMALIES: A CROSS-SECTIONAL COMPARATIVE STUDY. - Surpam, Karishma Khushalrao; Mandavi, Ujjwal (Student’s Journal of Health Research Africa, 2025)
Background Prenatal detection of fetal anomalies is critical for early diagnosis, parental counseling, and clinical management. While ultrasound (USG) is the first-line imaging modality, magnetic resonance imaging (MRI) is increasingly utilized as a complementary tool, especially in complex or ambiguous cases. Objectives To compare the diagnostic accuracy of ultrasound and magnetic resonance imaging (MRI) in detecting fetal anomalies and evaluate the concordance of each modality with final postnatal or autopsy-confirmed diagnoses. Methods This cross-sectional study included 50 pregnant women with suspected fetal anomalies. All participants underwent detailed ultrasound and fetal MRI between 24 and 34 weeks of gestation. Imaging findings were independently evaluated by experienced radiologists. The final diagnosis was established through postnatal examination or autopsy. Sensitivity, specificity, accuracy, and inter-observer agreement (Kappa statistics) were computed for each modality. Results The mean maternal age was 26.4 ± 4.2 years, and the mean gestational age at imaging was 28.1 ± 2.6 weeks. MRI detected 45 of 50 confirmed anomalies, demonstrating higher sensitivity (90.0%), specificity (95.6%), and accuracy (92.0%) compared to ultrasound (76.0%, 91.3%, and 80.0%, respectively). MRI outperformed ultrasound in detecting central nervous system (95% vs. 70%), thoracic (100% vs. 66.7%), and genitourinary anomalies (100% vs. 75%). Inter-observer agreement was greater for MRI (κ = 0.86) than for USG (κ = 0.74). MRI required a longer scan time (35 ± 8 min vs. 20 ± 5 min), and 88% of patients tolerated the MRI procedure well. Conclusion MRI provides superior diagnostic performance over ultrasound in the prenatal evaluation of fetal anomalies, particularly in central nervous system and thoracic abnormalities. It serves as an effective adjunct in cases where ultrasound findings are inconclusive. Recommendations MRI should be considered a complementary imaging modality in prenatal diagnostics, especially when ultrasound results are ambiguous or suggest central nervous system or thoracic anomalies.